Language self-concepts and causal attributions for performance in Chinese language and English language of pupils in a secondary school - Ong, Teck Chin. (2009)
Two instruments, one for assessment of Language Self-Concept and the other, for assessment of Causal Attributions were devised for the study of pupils Language Self-Concepts and Attribution Patterns with regards to their performance in the Chinese Language and the English Language. The original Language Self-Concept instrument for the two languages and the Causal Attribution instrument were piloted in two secondary boys schools. Data collected from the pilot study were factor analyzed with varimax rotation. The final instrument assesses the Chinese Language Self-Concept and the English Language Self-Concept. Each Language Self-Concept consisted of items which are associated with the following variables : Ability, Oral Skills, Written Skills and Effort and all the items together describe the Total Language Self-Concept of the language concerned. Similarly, the final Causal Attribution instrument consisted of items for each language. The items assess the attribution for failure and success in language performance.